2007
DOI: 10.1590/s0102-311x2007000300028
|View full text |Cite
|
Sign up to set email alerts
|

Avaliação da qualidade das variáveis epidemiológicas e demográficas do Sistema de Informações sobre Nascidos Vivos, 2002

Abstract: O trabalho avalia a qualidade da informação do Sistema de Informações sobre Nascidos Vivos (SINASC) quanto à clareza metodológica da documentação, completitude do preenchimento e consistência para o país, grandes regiões e Unidades da Federação no ano 2002. Adicionalmente, correlaciona-se a completitude com indicadores de pobreza, desigualdade e recursos humanos. As variáveis analisadas são: raça/cor do recém-nascido, instrução materna, estado civil materno, ocupação materna, idade materna, consulta pré-natal,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
60
2
101

Year Published

2009
2009
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 140 publications
(167 citation statements)
references
References 32 publications
4
60
2
101
Order By: Relevance
“…SINASC database has good-to-excellent data completeness and shows good consistency for most variables despite data completion problems. 19 The analysis of this cohort showed that the neonatal mortality rate was about half of the national average rate in 2003, which is still high compared to rates in developed countries. Higher rates of early neonatal deaths are corroborates in other studies.…”
Section: Resultsmentioning
confidence: 82%
See 1 more Smart Citation
“…SINASC database has good-to-excellent data completeness and shows good consistency for most variables despite data completion problems. 19 The analysis of this cohort showed that the neonatal mortality rate was about half of the national average rate in 2003, which is still high compared to rates in developed countries. Higher rates of early neonatal deaths are corroborates in other studies.…”
Section: Resultsmentioning
confidence: 82%
“…Living in poor areas can have negative effects on children's health. 19 Traditional models of analysis assume independence of observations and homogeneity of variance but they do not take into account a hierarchy of predictors, i.e., observations originated from the same unit may be more similar than those coming from different units. It can lead to overestimation of clustering effects and inaccurate conclusions.…”
Section: Introductionmentioning
confidence: 99%
“…O SINASC foi criado no início dos anos 1990 e, desde então, vários esforços foram feitos no sentido de superar suas principais dificuldades no que se refere a cobertura 13 , confiabilidade 1,14 e completitude das informações 3,9 . Ademais, a ampla disseminação da informação pelo DATASUS possibilitou maior utilização dos dados por gestores e pesquisadores, propiciando, conseqüentemente, a identificação de alguns problemas, o que levou a novas críticas e melhora nas informações 4 .…”
Section: Discussionunclassified
“…Valendo-se dessas informações, foi calculado o percentual de municípios que apresentavam um grau de preenchimento considerado excelente (> 95%), tendo como base o sistema de escores proposto por Romero & Cunha 9 . Esses autores adotaram como ponto de referência para avaliar a incompletitude os seguintes escores: excelente, quando a variável apresentava menos de 5% de preenchimento incompleto, bom (5% a 10%), regular (10% a 20%), ruim (20% a 50%) e muito ruim (mais de 50%).…”
Section: Métodounclassified
See 1 more Smart Citation